Our Living Manhood : Literature, Black Power, and Masculine Ideology - Murray, David, 1945- (Book collections on Project MUSE., 2007)
Matter, Magic, and Spirit explores the ways religious and magical beliefs of Native Americans and African Americans have been represented in a range of discourses including anthropology, comparative religion, and literature.